Relative vibration attenuation by means of self‐active devices constituted by permanent magnets separated by silicone layers. Issue 5 (26th July 2016) - Ricciardi, Enrico; Ausanio, Giovanni; Iannotti, Vincenzo; Pasquino, Vittorio; Silvestri, Brigida; Lanotte, Luciano
Summary: The relative vibrations of two small frames with different stiffness, subjected to the same oscillating excitation coming from their base platform, were investigated. The effects of the innovative coupling of standard passive attenuation and time variation of magnetic forces (self‐produced by the vibration itself) were investigated. The first experimental tests demonstrate that the amplitude of relative vibration can be easily decreased up to 75% without requiring external energy. In perspective, by varying the attenuator shape and power, it is possible to use it in all the cases in which it is necessary to reduce the vibrations of a breakable or unstable structure inside a building accidentally exposed to vibration, such as a rotor inside a frame or a shelf in a museum room. Copyright © 2016 John Wiley & Sons, Ltd.